Valorisation of Natural Waste: Dam Sludge for Road Construction - A. Larouci, Y. Senhadji, L. Laoufi and A. Benazzouk (Nature Environment and Pollution Technology, 2020)
The Algerian dams are in a more or less silted state. Fergoug dam is the most silted dam since it records a rate of siltation of 95%. The siltation of the dam is undoubtedly the most dramatic consequence of the problem of erosion in Algeria. The investigations are at two levels: either prevent the solids to arrive in the dam (that is to put obstacles to break the forces of the runoff water, but we can only hope partial results) or the evacuation of sediments by appropriate management of bottom. But in our opinion, their valorisation in the field of construction is the most appropriate solution. This valorisation helps protect the environment and natural materials. Many mud treatment methods are often used to improve the insufficient geotechnical properties before reuse for a certain function in the structure. Lime treatment is one of the most common methods of converting soils to new materials that provide the desired performances. The objective of this work is to study the mud behaviour of the Fergoug dam (Algeria) for its use in the application of road engineering. The study consists of reconstituting samples of the Fergoug dam mud with various proportions of lime in the laboratory and subjecting them to various tests (Proctor, VBS, CBR index, DRX, etc.). The results obtained are encouraging and therefore allow the valorisation of sediments of the Fergoug dam which are a cumbersome waste for the environment.